The Pediatric Sinus Staging System: A Computed Tomography–Based Approach to Grading Pediatric Sinus Disease. (22nd May 2020) - Melder, Katie; Shaffer, Amber; Govil, Nandini; Stapleton, Amanda
Abstract : Objectives/Hypothesis: Pediatric chronic rhinosinusitis (CRS) is a prevalent disease with few objective measurements available to predict which patients will require surgical intervention. The Lund‐Mackay (LM) score for computed tomography (CT) scans is one objective data point available for the adult population; however, a dedicated scoring system in the pediatric population has not been popularized. We present a Pediatric Sinus Staging System (PSSS) that considers both opacification and the varying developmental stages of each sinus. Study Design: Retrospective chart review. Methods: We analyzed CT scans of pediatric patients with a diagnosis of CRS. Both LM and PSSS scores were calculated for each scan. Groups were formed based on treatment outcomes and included patients who were treated successfully with medical therapy and/or adenoidectomy (med/adenoid), patients who required functional endoscopic sinus surgery (FESS), and patients who required revision FESS. Results: Overall, 76 patient scans were reviewed. PSSS values were significantly less than LM for the control group ( P  = .001) and significantly higher for patients with cystic fibrosis ( P  = .027) and with CRS with polyps ( P  = .001). The ideal cutoff for PSSS to distinguish between med/adenoid and single FESS treatment with a sensitivity 90.6% and specificity of 50.0% was ≥2. Conclusions: The PSSS gives a more descriptive score by accounting for the opacification and pneumatization of each sinus. Our current results show similar values between PSSS and LM scores, which suggests internal validity. In addition, a PSSS score of ≥2 may help physicians better counsel families on the likelihood of requiring FESS. Further investigation is needed to fully validate the PSSS. Level of Evidence: 3b Laryngoscope, 131:E642–E648, 2021